Comparing of Frequent Central Venous Catheter Insertion and Selection Procedure and its Complications - Ala, Alireza; Shams Vahdati, Samad; Paknezhad, Seyed Pouya; Dare, Mina; Aghili, Alireza (Annals of Anesthesiology and Critical Care, 2017)
Background: Central venous catheterization is used for several goals in the emergency department. Common sites of insertion of central venous lines are the right and left jugular veins as well as the right and left subclavian veins. The aim of this study was to evaluate the tendency frequency of emergency medicine residents to choose central venous line insertion route and also to determine the post-procedure complications. Methods: In this descriptive cross-sectional study, all patientswhounderwent central venous catheterization and were in the emergency ward of the Imam Reza hospital, Tabriz, Iran during March 21, 2015 to September 23, 2015 were included, preferences route of insertion and complications of both right and left jugular and subclavian veins were descriptively analyzed. Results: Of all the 134 evaluated patients, 54.5% were catheterized in course of shock. 88.1% of patients underwent right jugular vein catheterization and only 4.5% experienced post-procedure complications. In 91.8% of cases, the decision-making was done by the physician and 75.4% of the catheterizations were fulfilled by second-year emergency medicine residents. Conclusions: The most common route of catheterization was through the right jugular vein. Additionally, the most common complication was hematoma of the insertion site. In most of the cases, decision making was made by the physician and most of the catheterization procedures were fulfilled by second-year emergency medicine residents.